2008
DOI: 10.1137/070711177
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Functional Differential Equations with Applications to Compartmental Systems

Abstract: We study the monotone skew-product semiflow generated by a family of neutral functional differential equations with infinite delay and stable D-operator. The stability properties of D allow us to introduce a new order and to take the neutral family to a family of functional differential equations with infinite delay. Next, we establish the 1-covering property of omega-limit sets under the componentwise separating property and uniform stability. Finally, the obtained results are applied to the study of the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Novo, Obaya and Sanz [35] have shown that the omega limit set is a uniformly stable minimal set which admits a fiber distal flow extension if its semiorbit is uniformly stable, which not only extends the classical extension result in Shen and Yi [39], but also drops the distal assumption in the abstract result in [29]. Later, together with their topological result with this Lyapunov integer-valued function method, they have investigated a series of functional differential equations with infinite delay and obtained one covering property of the base space ( [35,33]), some of which are even new in autonomous/periodic cases. The idea in [38] is also along these lines.…”
Section: Introductionmentioning
confidence: 74%
“…Novo, Obaya and Sanz [35] have shown that the omega limit set is a uniformly stable minimal set which admits a fiber distal flow extension if its semiorbit is uniformly stable, which not only extends the classical extension result in Shen and Yi [39], but also drops the distal assumption in the abstract result in [29]. Later, together with their topological result with this Lyapunov integer-valued function method, they have investigated a series of functional differential equations with infinite delay and obtained one covering property of the base space ( [35,33]), some of which are even new in autonomous/periodic cases. The idea in [38] is also along these lines.…”
Section: Introductionmentioning
confidence: 74%
“…In this section, we develop a stochastic field theory as in [84] for capturing neural activity in order to analyze system multistability. In the next section, we extend the results of this section to additionally address time delay functional models [85] in order to account for time delay and memory effects in inhibitory and excitatory networks.…”
Section: Stochastic Multistability For a Mean Field Synaptic Drive Fimentioning
confidence: 97%
“…As explained before, this paper provides a contribution to the dynamical theory of monotone recurrent skew-product semiflows. We consider a monotone structure on Ω × BC determined by an exponential ordering and we enhance the theory started in [15], [18] and [17], where the 1-covering property of omega-limit sets of relatively compact trajectories was proved.…”
Section: Functional Differential Equations With Infinite Delaymentioning
confidence: 99%
“…We omit the proof of the following result, which can be easily adapted to this case from Theorem 2.5 of Muñoz-Villarragut [27]. As stated before, given a continuous function x ∈ C(R, R m ), x t (•) denotes the continuous function…”
Section: Transformed Exponential Order For Nfdes With Infinite Delaymentioning
confidence: 99%
See 1 more Smart Citation